The Genus Acer in Nepal - Manandhar, Vidya K. (Journal of Plant Resources, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The paper includes 12 species of Acer recorded from Nepal. A key for identification of species, their description and distribution have been provided. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 58-67